Wie is die sondaar? Die beskouing van Karl Barth - Zyl, F. J. van (Hervormde teologiese studies, 1994)
Who is the sinner? The view of Karl Barth The previous article dealt with Barth’s view of the knowledge and real essence of sin, while this one focus on his view of the human being as sinner. In accordance with his christological approach to all theological matters, Barth presents us with a description of the image and character of the sinner as mirrored by the obedient suffering and death of Jesus Christ on the cross in the place of all sinners of all times - past, present and future. The price that God paid in surrendering his only Son to such suffering, indicates the enormous guilt and baseness of every sinner. Every human being is utterly insolvent and can only be delivered from sin through God’s graceful remission of siru